Estrogenic Activity of Ethanolic Extract of Papaya Peels (Carica Papaya L.) on Uterine Weight and Mammae Gland Proliferation on Ovariectomy Rats - Dhania Novitasari; Devyanto Hadi Triutomo; Fitriana Hayyu Arifah; Anselma Ivanawati; Zahrotul Ulum; Retno Murwanti (Indonesian Society for Cancer Chemoprevention, 2018)
Papaya bark is one of Indonesia's natural wealth that contains flavonoid compounds such as myricetin and kaempferol that included in the phytoestrogen compounds. The aim of this study is to examine the estrogenic effects of ethanolic extract of papaya peels (EEPP) on the development of mammae gland and the increasing of uterine weight. The in vivo test was performed in ovariectomized Sprague Dawley female rats. After 30 days of treatment, animals were sacrificed to take the uterus and mammae glands. Measurement of uterine weight and mammae gland was observed by hematoxylin-eosin staining method to know the lobulus development and AgNOR staining to determine the proliferation level of mammae gland epithelial cells. The results showed that EEPP at the concentrations of 500 and 1000 mg/kgBW were able to increase uterine weight and proliferation of mammae gland. In conclusion, papaya bark has the potential as phytoestrogen compound to maintain female reproductive health and woman beauty.Keywords : Ethanolic extract of papaya peels (EEPP), phytoestrogen, ovariectomized rats, uterine weight, mammae proliferation